Utilization of Sika Viscocrete 8670mn for High Performance Concrete Using Local Materials - Michael Cang; Yusra Aulia Sari (Fakultas Teknik Sipil dan Perencanaan, 2023)
The Riau Archipelago is a non-volcanic area surrounded by the sea and directly adjacent to the North Natuna Sea. Thus the supply of quality materials for concrete-based construction is not so good. As well as the development of Batam City which leads to high-rise buildings also shows a rapid increase in static development in Batam City. The main problem that occurs in the concrete industry in Batam City is the supply of materials that can be used for high performance, in other words the materials used in the Batam area have insufficient capacity to be developed further. So on this occasion the author has the idea to develop local materials with the addition of admixture to increase compressive strength, slump retention, to the economic value of concrete. Good concrete is concrete that has criteria such as ease of work, a stable compressive strength value, and is able to reduce the carbon content removed during concrete processing. Because modern concrete must reduce air and liquid solid waste generated from its processing. In addition to these factors, good concrete must also consider the economic value and the effects of the surrounding environment.